(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Income of Siamese Pumpkin Farming as the Main Commodity of Farmers in Sukawana Village, Kintamani District, Bangli Regency. The development of agriculture in Sukawana Village is characterized by the phenomenon of switching the main commodity from orange to chayote which is done by the majority of farmers in Sukawana Village. The purpose of this study was to determine 1) analyze the income of chayote farming as the main commodity of farmers in Sukawana Village, Kintamani District, Bangli Regency, 2) analyze the feasibility of chayote farming as the main commodity of farmers in Sukwana Village, Kintamani District, Bangli Regency. The sample of this study amounted to 30 respondents using purposive sampling technique. Data in this study were obtained through interviews and observations. The data obtained were analyzed using the formula of production costs, revenue, income and farm feasibility analysis. The results showed that the income obtained from chayote farming cultivated by Sukawana Village farmers with an average area of 0.25 Ha amounted to Rp.60,760,000 with R/C Ratio value of 3,92. in this study it can be concluded that the income of chayote farming with an average area of 0.25 Ha for one year amounted to Rp.60,760,000 with an R / C ratio value of 3.92 which means that the farm is feasible.